In-situ observation of silk nanofibril assembly via graphene plasmonic infrared sensor - Wu, Chenchen; Duan, Yu; Yu, Lintao; Hu, Yao; Zhao, Chenxi; Ji, Chunwang; Guo, Xiangdong; Zhang, Shu; Dai, Xiaokang; Ma, Puyi; Wang, Qian; Ling, Shengjie; et al. (Nature communications, 2024)
Silk nanofibrils (SNFs), the fundamental building blocks of silk fibers, endow them with exceptional properties. However, the intricate mechanism governing SNF assembly, a process involving both protein conformational transitions and protein molecule conjunctions, remains elusive. This lack of understanding has hindered the development of artificial silk spinning techniques. In this study, we address this challenge by employing a graphene plasmonic infrared sensor in conjunction with multi-scale molecular dynamics (MD). This unique approach allows us to probe the secondary structure of nanoscale assembly intermediates (0.8–6.2 nm) and their morphological evolution. It also provides insights into the dynamics of silk fibroin (SF) over extended molecular timeframes. Our novel findings reveal that amorphous SFs undergo a conformational transition towards β-sheet-rich oligomers on graphene. These oligomers then connect to evolve into SNFs. These insights provide a comprehensive picture of SNF assembly, paving the way for advancements in biomimetic silk spinning. Here, the authors develop a graphene plasmonic infrared sensor to probe the secondary structure of nanoscale assembly intermediates and the morphological evolution of silk nanofibrils, the fundamental building blocks of silk fibres.